EVALUASI PROGRAM PRAKTIK KERJA LAPANGAN KOMPETENSI KEAHLIAN TEKNIIK PENDINGIN DAN TATA UDARA SE-KOTA BEKASI - Sahara, Siti (Jurnal Pendidikan Teknik dan Vokasional, 2021)
The aims of this research is to know about the effectiveness of Field Practice Programs by cooler technic and air conditioner competency in Bekasi academic year 2016-2017. It is evaluation research with CIPP evaluation model method with 4 components such as context, input, process and product. This research use purposive sampling technique with 66 students as object of study, 10 people from school and 6 DU/DI instructors. Technique of collecting data by observation, questionnaires, and documentation. Data analysis using Huberman model and mixed methods.. The result of the research shows : (1) context evaluation: there is imbalance between the number of MOU that owned by school and the number of PKL participants; (2) input evaluation: a) there is no curriculum implementation that arranged by cooperation of school and industry, b) Less of teacher’s participation as supervisor both when training held by government or industry; (3) process evaluation: a) 18% participant of PKL in non-cooler technic and air conditioner engineering industry, b) 23% participants do PKL less than 1 semester (about 3 months) in line with Permendikbud act 60 of 2014; (4) product evaluation: a) 65 % participants have very good category in work assessment, b) the effectiveness of PKL in very good category (83%) and the changes of performance known by the present of students before and after of PKL. Keywords: air conditioning, cooling, evaluation, learnes, practice.